2021
DOI: 10.1186/s13023-021-01694-8
|View full text |Cite
|
Sign up to set email alerts
|

Dalfampridine in the treatment of multiple sclerosis: a meta-analysis of randomised controlled trials

Abstract: Background Multiple sclerosis (MS) is a chronic illness involving the central nervous system (CNS) that is characterised by inflammation, demyelination, and degenerative changes. Dalfampridine is one of the available treatments for MS symptoms and comorbidities. This meta-analysis aimed to assess the safety and benefits of dalfampridine versus placebo in MS by summarising data deriving from previously published clinical randomised controlled studies (RCTs). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…A mislocation of Kv is described in demyelinating areas of the MS brain [ 121 ]. Of note, the I A K + channel blocker Dalfampridine improves walking in MS patients and was approved by the FDA in 2010 [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mislocation of Kv is described in demyelinating areas of the MS brain [ 121 ]. Of note, the I A K + channel blocker Dalfampridine improves walking in MS patients and was approved by the FDA in 2010 [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, administration of a Kv1.1 selective blocker (BgK-F6A) ameliorates disease course in EAE mice [ 75 ], and treatment with the I A blocker 4-AP enhances axonal conduction [ 76 ]. As I A is widely diffused along demyelinated axons and contributes to MS symptoms [ 155 ], in 2010 dalfampridine, an extended-release form of 4-AP, has been approved by the FDA to improve walking in MS patients [ 77 ]. The mechanism by which Kv blockers could exert neuroprotection is ascribed to the block of excessive K + outflow from axons causing extracellular K + homeostasis outbalance that postpones the K + reversal potential to more positive values.…”
Section: Voltage-gated Channels In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
“…Low dose 4-AP treatment initiated one day after peripheral nerve crush resulted in significant gait improvement at 3 days post-injury that progressed through 8 days, although a significant increase in nerve conduction velocity was not observed until 21 days (Tseng et al, 2016). Furthermore, clinical trials of 4-AP (dalfampridine) for patients with chronic MS used a treatment duration of 4 weeks or more to evaluate improvement of function (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our studies of white matter injury revealed axon and myelin damage that included disruption of nodal regions and slowed conduction velocity early after TBI (Mierzwa et al, 2015; Marion et al, 2018). These findings resemble aspects for which 4-aminopyridine (4-AP) was developed to treat patients with MS. 4-AP is prescribed for patients in the chronic stage of MS and responders have positive effects on walking ability, finger dexterity, and cognitive function (Zhang et al, 2021). Recent pre-clinical testing on acute peripheral nerve injuries, which also involve axon and myelin damage, revealed the surprising result that 4-AP treatment enhances structural recovery of axons and myelin (Tseng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additional drugs that were identified in females only included two drugs used to treat inflammatory conditions, hydrocortisone and famotidine, of which famotine already had shown effectiveness in reducing positive schizophrenia symptoms [95], but its potential effects on cognitive symptoms in schizophrenia have not been studied. Moreover, dalfampridine has shown procognitive effects in patients with multiple sclerosis [96], and acetylcysteine has already been suggested to be effective for cognitive symptoms in schizophrenia [97]. The potential procognitive effects of acetylcysteine in schizophrenia may probably be mediated by various anti-inflammatory and neuroprotective processes [97].…”
Section: Discussionmentioning
confidence: 99%